Quasi-periodicity and multi-scale resonators for the reduction of seismic vibrations in fluid-solid systems. (December 2016) - Carta, Giorgio; Movchan, Alexander B.; Argani, Luca P.; Bursi, Oreste S.
Abstract: This paper presents a mathematical model for an industry-inspired problem of vibration isolation applied to elastic fluid-filled containers. A fundamental problem of suppression of vibrations within a finite-width frequency interval for a multi-scale fluid-solid system has been solved. We have developed a systematic approach employing full fluid-solid interaction and dispersion analysis, which can be applied to finite and periodic multi-scale systems. The analytical findings are accompanied by numerical simulations, including frequency response analyses and transient regime computations.